Toward better use of inoculants in the humid tropics - Ayanaba, A. (John Wiley & Sons, 1977)
The use of inoculants in the humid tropics must be considered on the one hand, against a background of undependable and inadequate supplies of nitrogen fertilizers and an infrastructure characterized by unreliable transportation and inadequate finances and, on the other, against the cheap and dependable symbiotically fixed N2 resulting from proper legume seed inoculation. Inoculants are used mainly in the humid tropics on introduced grain legumes. Indigenous legumes seldom respond to inoculation and forage and soil-conserving legumes are largely ignored.. Certain environmental factors are associated with the use of inoculants and these militate against the realization of the advantages of inoculants. In the humid tropics the periods during which these factors can affect inoculant quality are very important. These periods occur (a) during transportation and storage,(b) before inoculated seed is sown, and (c) after sowing when Rhizobium is exposed to soil microorganisms and the soil environment. These factors are discussed. Maintenance of culture collections for inoculant production is recommended.